Experiential Learning for Groundwater Governance in India: Groundwater Game Surveys - International Food Policy Research Institute; Foundation for Ecological Security; International Crops Research Institute for the Semi-Arid Tropics (International Food Policy Research Institute, 2025)
The Scaling up experiential learning tools for sustainable water governance project aims to enhance the capacity of Indian communities to sustainably manage water resources. The intervention combined collective action games, participatory planning tools, and community debriefings to promote behavioral shifts toward sustainable groundwater and surface water management. These tools are designed to support informed decision-making, foster collective action, and strengthen governance of water as a common resource.